2021
DOI: 10.1007/s42844-021-00037-7
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Parents and Primary Caregivers by Sex and Associated Child Health Indicators

Abstract: Poor mental health among parents or primary caregivers is associated with poor mental and physical health in children; however, research often excludes the mental health of male caregivers including fathers. This analysis examines associations between caregiver mental health by caregiver sex and child health indicators (i.e., child's general health; child's history of diagnosed mental, behavioral, or developmental disorders (MBDDs)). Using parent-reported data on 97,728 US children aged 0-17 years from the Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…BMI also did not differ between clusters, indicating a lack of support for the hypothesis that maternal mental health and child BMI were inversely related. Similar to previous research, as hypothesized, the current study findings show that as mothers’ mental health status became poorer, children’s general health and mental health quality of life declined [ 100 , 101 ]. Additionally, inadequate sleep and poor sleep quality are correlated with poorer mental health, which is consistent with the current study’s findings [ 4 , 5 , 47 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…BMI also did not differ between clusters, indicating a lack of support for the hypothesis that maternal mental health and child BMI were inversely related. Similar to previous research, as hypothesized, the current study findings show that as mothers’ mental health status became poorer, children’s general health and mental health quality of life declined [ 100 , 101 ]. Additionally, inadequate sleep and poor sleep quality are correlated with poorer mental health, which is consistent with the current study’s findings [ 4 , 5 , 47 ].…”
Section: Discussionsupporting
confidence: 88%
“…Maternal mental health is closely related to that of children in the family and can affect children’s development and behaviors [ 100 , 101 ]. Maternal mental health is linked to the inability to effectively or consistently parent, in turn contributing to negative weight-related parenting behaviors, including an increased likelihood of providing children with low-nutrient-dense foods and giving less encouragement at family mealtimes [ 16 , 23 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…27 Caregiver mental health is closely linked with their child's mental health, and caregivers with poorer mental health are more likely to report unmet needs for mental health services for their child. 28,29 Finally, expanding the definition of unmet need to include children who needed specialty mental health services but could not get these services in the past 12 months (Appendix Table 1), we also found that unmet needs were more prevalent among children without insurance. This finding is similar to previous research linking insurance coverage to unmet needs for health care services.…”
Section: + Modelmentioning
confidence: 70%
“…As such, identifying risk factors associated with child mental health within the pandemic context should be a focus in research and public policy ( Chadi et al, 2022 ). Research shows that parental mental health struggles were associated with that of their children ( Wolicki et al, 2021 ) and that the COVID-19 context has been especially difficult for parents. For instance, in Canada, parents with children living at home reported higher levels of alcohol consumption, suicidal thoughts, anxiety and depression in comparison to those without children under their care ( Gadermann et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%